Distribution of urinary calculi and its association with clinical and laboratory findings in dogs and cats with stone analysis at Chulalongkorn Animal Teaching Hospital, Thailand (2020-2024) - Tanattha Ladabornvidhaya; Natkrita Baikloy; Theaparak Thipjaroen; Parapond Kongrakchang; Warisara Kaechaiya; Sumonwan Chamsuwan; Monkon Trisiriroj; Chollada Buranakarl (The Thai Journal of Veterinary Medicine, 2026)
Urinary calculi are commonly encountered in veterinary practice; however, information regarding their distribution of stone that underwent analysis and associated clinical findings remains limited. This study investigated the distribution of urolithiasis and the associations between stone types and clinical and laboratory findings in dogs and cats presented to the Chulalongkorn Small Animal Teaching Hospital between 2020 and 2024. The three most common stone types in both species were calcium oxalate (CaOx), struvite, and urate, with relatively stable trends over the 5-year period. Small-breed dogs had a higher risk of developing CaOx urolithiasis than medium-breed dogs (OR = 10.4, 95% CI = 4.64–22.45, P < 0.001), whereas medium-breed dogs were at greater risk for urate (OR = 8.0, 95% CI = 2.98–22.93, P < 0.001) and cystine urolithiasis (OR = 92.9, 95% CI = 13.59–1021, P < 0.001). Uroliths were most commonly found in the urinary bladder of older intact male dogs and neutered male cats. Calcium oxalate uroliths were associated with the highest age at presentation and the longest recurrence period. Female dogs were 12.5 times more likely to develop struvite than CaOx urolithiasis. Compared with dogs with CaOx urolithiasis, dogs with struvite urolithiasis more frequently exhibited anorexia, urinary incontinence, hematuria, higher urine pH, bacteriuria, pyuria, and increased white blood cell counts, suggesting urinary tract infection. Urinary crystals were infrequently detected despite confirmed urolithiasis and were not specific to stone type. These findings provide useful information for the diagnosis and management of canine and feline urolithiasis.